2004
DOI: 10.1783/147118904322995438
|View full text |Cite
|
Sign up to set email alerts
|

A novel therapy with testosterone and sildenafil for erectile dysfunction in patients on renal dialysis or after renal transplantation

Abstract: Background We undertook a prospective pilot study in a small cohort of patients with renal replacement therapy to determine the cause of erectile dysfunction (ED)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…30 For the latter effect, addition of T might have been useful because sexual desire is exquisitely sensitive to the action of T. 31 Indeed, in a study using combination therapy of sildenafil with T for ED in patients on HD or after renal transplantation, all patients had a good response to the combination of T and sildenafil, particularly hypogonadal patients. 12 Our study restoring circulating plasma T to midnormal levels was reasonably successful. In the study by Lawrence et al 11 administering depot injections, sexual function was fully restored in only three men (11.1%), and two gradually lost the response over 18 months.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…30 For the latter effect, addition of T might have been useful because sexual desire is exquisitely sensitive to the action of T. 31 Indeed, in a study using combination therapy of sildenafil with T for ED in patients on HD or after renal transplantation, all patients had a good response to the combination of T and sildenafil, particularly hypogonadal patients. 12 Our study restoring circulating plasma T to midnormal levels was reasonably successful. In the study by Lawrence et al 11 administering depot injections, sexual function was fully restored in only three men (11.1%), and two gradually lost the response over 18 months.…”
Section: Discussionmentioning
confidence: 69%
“…Subjects who scored o26 in this domain were considered to have ED. The score for each item ranges from 0 to 5 for questions 1-10, 0 meaning no sexual activity/no attempt to have sexual intercourse, and from 1 to 5 for questions [11][12][13][14][15]. The severity of ED was classified using five categories: no ED (EF score: 26-30), mild (EF score: [22][23][24][25], mild to moderate (EF score: 17-21), moderate (EF score: 11-16) and severe (EF score: 6-10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chatterjee and colleagues reported an improvement in sexual performance in all 12 patients on hemodialysis and post-renal transplant who had a median serum testosterone 329 ng/dL (11.45 nmol/L) and ED; these patients had monthly intramuscular testosterone cypionate 50 to 100 mg sildenafil orally once or twice weekly for 12 months. 20 Another study by the same group used similar drug regimen for 6 months in 8 bone marrow transplant patients; the authors demonstrated that combination therapy was safe and effective in high-dose chemotherapy recipients. Furthermore, sildenafil improved IIEF scores in hemodialysis patients with serum testosterone 300 ng/dL who failed initially with erythropoietin and/or testosterone for 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…17,19 Few uncontrolled studies have shown a beneficial effect when testosterone was added to PDE-5 inhibitors, however, the small sample size, lack of controls and the different serum testosterone cut-offs used made these studies subject to criticism. [20][21][22][23][24] A systematic review of the literature demonstrates that most trials examining combination therapy or testosterone alone suffer from methodological problems or report inconsistent results; these studies also show oral PDE-5 inhibitors may be enhanced by testosterone adjunction whenever necessary. 19 A relatively recent meta-analysis identified three small-randomized controlled trials in hypogonadal men with ED refractory to previous PDE-5 inhibitors.…”
Section: Introductionmentioning
confidence: 99%